Digital Transformation, Public Trust, and Banking Challenges: A Comprehensive Mixed-Methods Analysis - Rustan DM; Karlina Ghazalah Rahman; Emily Nur Saidy; Qomariyatus Sholihah; Sri Prilmayanti Awaluddin; Ridwan Danuarta Galisong (Institut Bisnis dan Informatika Kesatuan, 2026)
Digital transformation creates both opportunities and challenges for banks. The study aims to analyze the challenges and opportunities of digital transformation and public trust in Makassar’s banking sector and develop strategic recommendations to enhance its sustainability and competitiveness. By using a mixed-methods approach that combines qualitative and quantitative elements, this research explores various aspects, ranging from digital promotions, changes in consumer behavior, service quality, and collaboration between financial institutions. The SWOT analysis identifies strengths in effective promotion, opportunities in financial institution collaboration, weaknesses in service quality and digital education, as well as threats in infrastructure complexity and intensification of competition. Through the use of the MICMAC analysis tool, key factors are placed in the context of interdependence relationships and their impact on the banking system. The research results provide in-depth insight into the problems facing the banking sector in Makassar. A number of policy suggestions were proposed, including increasing digital promotion, digital financial literacy, collaboration with financial institutions, and continuous evaluation and monitoring. These policy recommendations can help the banking sector address digital transformation challenges and strengthen public trust. The SWOT and MICMAC analyses provide a foundation for developing effective strategies in the digital banking era.